P207 A quality improvement intervention to increase pneumococcal and influenza vaccination rates in immunosuppressed inflammatory arthritis patients. (20th April 2020) - Murray, Kieran; Low, Candice; Young, Francis; O'Rourke, Anna; Callanan, Ian; Feeney, Eoin; Veale, Douglas J
Abstract: Background: Pneumococcal and influenza vaccination rates have been suboptimal in studies of immunosuppressed patients. We aimed to assess barriers to and increase rates of 23-valent pneumococcal polysaccharide vaccine (PPSV23) and influenza vaccination in this group. Methods: In 2017, Rheumatology outpatients completed an anonymous questionnaire recording vaccination knowledge, status and barriers. Simultaneously, a low-cost multifaceted quality improvement (QI) intervention was performed. All outpatients on oral steroids, immunosuppressant conventional synthetic disease modifying antirheumatic drugs (csDMARDs) or biologics (bDMARDs) were included in the study. In 2018, post-intervention, the clinic was re-assessed. Demographics, diagnosis, medications, smart phone access and willingness to use this for vaccination reminders were assessed for independent vaccination predictors using binary logistic regression analysis. Results: 425 patients were included (72.6% rheumatoid arthritis, 74% women, 45.6% ≥60 years old). From 2017-2018, vaccination rates increased for PPSV23 {41.0% to 47.2% (p = 0.29)} and influenza {61.8% to 62.1% (p = 0.95)}. The most common reason for non-vaccination was lack of awareness. Following the intervention, this decreased for influenza (36.7% to 34.2%) and PPSV23 (82.1% to 76.4%). General Practitioners performed most vaccinations, only 3.6% were delivered in hospital. Significant predictors of PPSV23 vaccination were older age {≥80 years had an OR 41.66 (95% CI 3.69-469.8, P = 0.003), compared to ≤ 39 years}, bDMARD use (OR 2.80, 95% CI 1.24-6.32, P = 0.013) and adequate influenza vaccination (OR 9.01, 95% CI 4.40-18.42, P < 0.001). Up to date PPSV23 vaccination (OR 8.93, 95% CI 4.39-18.17, P < 0.001) predicted influenza vaccination. Conclusion: PPSV23 and influenza vaccination rates were suboptimal and increased marginally. Point-of-care vaccination may be more effective. Disclosures: K. Murray: None. C. Low: None. F. Young: None. A. O'Rourke: None. I. Callanan: None. E. Feeney: None. D. Veale: None.